A Western Dietary Pattern Is Associated with Poor Academic Performance in Australian Adolescents - Anett Nyaradi; Jianghong Li; Siobhan Hickling; Jonathan K. Foster; Angela Jacques; Gina L. Ambrosini; Wendy H. Oddy (Nutrients, 2015)
The aim of this study was to investigate cross-sectional associations between dietary patterns and academic performance among 14-year-old adolescents. Study participants were from the Western Australian Pregnancy Cohort (Raine) Study. A food frequency questionnaire was administered when the adolescents were 14 years old, and from the dietary data, a `Healthy' and a `Western' dietary pattern were identified by factor analysis. The Western Australian Literacy and Numeracy Assessment (WALNA) results from grade nine (age 14) were linked to the Raine Study data by The Western Australian Data Linkage Branch. Associations between the dietary patterns and the WALNA (mathematics, reading and writing scores) were assessed using multivariate linear regression models adjusting for family and socioeconomic characteristics. Complete data on dietary patterns, academic performance and covariates were available for individuals across the different analyses as follows: n = 779 for mathematics, n = 741 for reading and n = 470 for writing. Following adjustment, significant negative associations between the `Western' dietary pattern and test scores for mathematics (β = -13.14; 95% CI: -24.57; -1.76); p = 0.024) and reading (β = -19.16; 95% CI: -29.85; -8.47; p ≤ 0.001) were observed. A similar trend was found with respect to writing (β = -17.28; 95% CI: -35.74; 1.18; p = 0.066). ANOVA showed significant trends in estimated means of academic scores across quartiles for both the Western and Healthy patterns. Higher scores for the `Western' dietary pattern are associated with poorer academic performance in adolescence.
Keywords: 300; diet; academic performance; adolescence; Raine Study